KIAT MENINGKATKAN EFISIENSI MELALUI KEBAHAGIAAN BAWAHAN DALAM BEKERJA - Sjachril, lnriati (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2006)
Leadership, a short a word, easy to say, every one need leadership and everyone talks about leadership today, but not any people knows why, what and how is it exactly leadership. Not only just leadership but an effective and proper leadership.History records lots of evidence of how leadership plays a very important rule to anybody, not only to those who leads. A leader needs leadership, a sub ordinate needs leadership, An Individual is actually a leader, though not every leader has leadership. Leader who doesnât have leadership would be ignored, leader who has leadership but arenât able to properly apply it would also be ignored.Leadership is not a constant requiring fixed abilities or a fixed pattern. It depends on a) the leader philosophy or his own value system, b) the type of his follower and c) the situations in which it is to be exercised. In the, the leader has to play a particular role depending on his follower and the situation in which the leadership is being exercised.